Pengaruh Coaching Dan Mentoring Terhadap Perkembangan Umkm Fashion Serta Orientasi Yang 1 1 Dimediasi Kewirausahaan - Danang Rifai; Ratnasari Dewi; Amelia Kartika (UNIVERSITAS RAHARJA, 2021)
The purpose of this study is: to examine the effect of coaching and mentoring on the development of UMKM Fashion in supporting areas of the capital city. This research was conducted at UMKM Fashion conducted by young men and women of the millennial generation. While the study population was reviewed at SMEs Fashion in the Greater Tangerang area. The sample of this study consisted of 70 UMKM Fashion Distros in Tangerang Regency, Tangerang City and South Tangerang City. The sampling technique is multistage sampling which consists of the first simple random sampling in order to determine the greater Tangerang area that has UMKM Fashion, the second is purposive sampling in order to determine the sample in each mapping area that has been determined as a member of the coaching and mentoring of the local entrepreneurship body, and the third convenience sampling method used in determining samples based on respondents selected in stage two who were willing to attend. At the time of sampling activities researchers will collaborate with representatives of leading fashion business associations associations in each region. Data collection using a questionnaire system. The statistical methods used by researchers are the Confirmatory Factor Analysis (CFA) Method for testing validity, the Cronbach Alpha Method for testing reliability, and the Baron & Kenny method for testing hypotheses. In this study, researchers obtained a research result that showed that coaching and mentoring had a positiveeffect on the development of Fashion UMKM and the Regional Entrepreneurship Agency played a positive role in mediating the development of UMKM.